The invasive Indian bullfrog Hoplobatrachus tigerinus on the Andaman Islands : evaluating drivers of distribution, density, and trophic impact of an early stage invader - Mohanty, Nitya Prakash (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.